Evolution characteristics of metallurgical coals for coke making through thermogravimetric-mass spectroscopic measurements. Issue 6 (December 2021) - Kundu, Niloy; Biswas, Pinakpani; Bhunia, Prasenjit; Ghosh, Rita; Sarkar, Supriya
Abstract: Simultaneous thermogravimetric – mass spectrometry (TG-MS) analysis of pyrolytic decomposition of different metallurgical coals used in steel industries were carried out for better understanding of the coking mechanism during the carbonisation of coking coals. The investigation was performed at temperatures up to 1100 0 C in an argon atmosphere at a heating rate of 3 0 C/minute to simulate the coke plant scenario. Small amount (1 wt%) phenolic resin was introduced in selected coal to understand the pyrolytic behavior related to coking potential. The TG-MS experimental results showed that addition of resin to coal enhanced fluidity and thermal cracking accompanied by aromatization and poly-condensation process. It reveals the mechanism and characteristics of gases evolved and in some cases also helped to eliminate the discrepancy occurring for the same molecular weight components. Graphical Abstract: ga1 Highlights: Thermogravimetric-mass spectroscopy of coal pyrolysis revealed coking mechanism during coal pyrolysis. Evolution characteristics during carbonization of coking coal has been explored. Addition of resin has converted low rank coking coal into high rank coking coal. It gives an alternative to use low cost coal in steel Industry for coke making process. It also explains some volatile emission characteristics in coking process.